The geospatial web : (Springer, 2007)
This book summarizes the latest research on the Geospatial Web’s technical foundations, describes information services and collaborative tools built on top of geo-browsers, and investigates the environmental, social and economic impacts of geospatial applications. The role of contextual knowledge in shaping the emerging network society deserves particular attention. By integrating geospatial and semantic technology, such contextual knowledge can be extracted automatically – for example, when processing Web documents to identify relevant content for customized news services.